MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA PADA MATERI BANGUN RUANG MELALUI PEMANFAATAN ALAT PERAGA - Tatang Tatang (Universitas Galuh, 2021)
ABSTRACTOne of the efforts to increase students' motivation, activeness, and interest in mathematics is by using teaching aids during on-going learning. The use of teaching aids can improve the quality of learning and help students understand the concept of the material being studied which will have an impact on increasing student learning outcomes. This study ha a purpose was to describe the increase in mathematics learning outcomes of grade VI SD Negeri Tamansari Kota Tasikmalaya on geometry through the use of teaching aids. This research is a classroom action research conducted on 19 grade students. The research was conducted in two cycles. Each cycle consists of stages of planning, action, observation, and reflection. The instruments used were tests and student observation sheets. Based on the results of the study, it was obtained that the average value of mathematics increased in the first cycle of students who met the Minimum Completion Criteria (KKM) as many as 5 students or 25% while the other 75% were not yet complete so the study continued to cycle II. In the second cycle student learning outcomes experienced a significant increase, namely 100% of students had achieved completeness. The average score of students also increased in the first cycle of 58.5, while the average score in the second cycle was 80. These results have met the established success criteria so that it can be said that the use of teaching aids in learning materials for geometry can improve the results. student learning.Keywords: Learning Outcomes, Geometry, Teaching AidsABSTRAKSalah satu upaya guna meningkatan motivasi, keaktifan, dan minat siswa pada matematika yakni dengan menggunakan alat peraga pada saat pembelajaran belangsung. Penggunaan alat peraga mampu meningkatkan kualitas pembelajaran dan membantu siswa dalam memahami konsep materi yang dipelajari yang akan berdampak pada meningkatnya hasil belajar siswa. Penelitian dilaksanakann bertujuan guna memberikan deskripsi peningkatan hasil belajar matematika siswa kelas VI SD Negeri Tamansari Kota Tasikmalaya pada materi bangun ruang dengan memanfaatkan alat peraga. Penelitian termasuk tindakan kelas dimana pelaksanaannya pada siswa kelas VI yang jumlahnya 19 orang. Pelaksanaan penelitian dilakukan dua siklus. Masing-masing siklus terdiri dari tahapan perencanaan (planning), tindakan (action), pengamatan (observation), dan refeleksi (reflection). Instrumen yang digunakan adalah tes dan lembar observasi siswa. Berdasarkan hasil penelitian diperoleh data nilai rata-rata matematika mengalami peningkatan pada siklus I siswa yang memenuhi Kriteria Ketuntasan Minimum (KKM) adalah sebanyak 5 orang siswa atau sebesar 25% sedangkan 75% lainnya belum tuntas sehingga penelitian dilanjutkan ke siklus II. Pada siklus II hasil belajar siswa mengalami peningkatan yang signifikan yaitu 100% siswa sudah mencapai ketuntasan. Rata-rata nilai siswa juga mengalami peningkatan pada siklus I sebesar 58,5 sedangkan perolehan nilai rata-rata pada siklus II sebesar 80. Hasil tersebut sudah memenuhi kriteria keberhasilan yang ditetapkan sehingga dapat dikatakan bahwa penggunaan alat peraga pada pembelajaran materi bangun ruang dapat meningkatkan hasil belajar siswa.Kata Kunci: Hasil Belajar, Materi Bangun Ruang, Alat Peraga